Evaluation of User Satisfaction in Using the Emergency Department Information System (EDIS) from User’s Perspective - Shiow-Luan Wang; Jo-Yun Tsui (Engineering proceedings, 2023)
The service industry depends on Internet development that always changes. The changing service environment provides a range of opportunities to develop new information technology to communicate with customers and add new channels to reach all service providers. Hospital administration pays attention to improving medical service quality and using information systems for clinical care. A nursing information system is the most important part of the whole medical care information system. The aim of this study is to explore the key factors of user interface (UI) and the function of the emergency department information system (EDIS) from the viewpoint of the user’s operation. The questionnaire design is based on literature reviews and invited academic and industry scholars to conduct a pre-test for the validity of the content. The staff of a regional teaching hospital in central Taiwan were taken as the research subjects The study was based on the information system success model proposed by DeLong and McLean in 2003. In order to understand the use of information systems in hospitals, the TAM (technology acceptance model) is used to investigate the factors that influence the acceptance of new technology. A survey was conducted on the employees who are using the EDIS at present. There are four categories of participants: attending physicians, nurses, specialist nurses, and secretaries/registers. The results indicate that “user satisfaction” affects the success of the EDIS. For the question, “emergency medical information system has more benefits than traditional paper”, respondents gave good marks. For the question, “the stability of the emergency medical information system is very satisfactory“ was given the lowest. The aspects of the information system success model for the terms “system quality”, “information quality”, “service quality”, etc. were analyzed. User satisfaction is positively related, although user education is different. The reference data allow hospital administrators to consider the needs of users while developing or conversing about new systems for the future.